Challenges and Cybersecurity Solutions in the Era of Big Data and Artificial Intelligence - Abdul Robi Padri; Erwin Iskandar (Al-Makki Publisher, 2025)
The development of big data and artificial intelligence (AI) technology has brought about fundamental transformations in data management and utilization across various sectors. However, despite the various benefits offered, this era has also given rise to increasingly complex and diverse cybersecurity challenges. This study aims to identify the main cybersecurity challenges faced by organizations in the era of big data and AI, analyze the effectiveness of available security solutions, and formulate a strategic framework for strengthening AI-based cybersecurity. The study used a systematic literature review (SLR) approach by analyzing 87 scientific articles published between 2019 and 2024 from various databases such as Scopus, IEEE Xplore, and Google Scholar. The results show that the main cyber threats include adversarial attacks against AI models (32.4%), massive data leaks (28.7%), and AI-based ransomware attacks (21.5%). The most effective solutions include implementing a Zero Trust Architecture framework, machine learning-based threat detection, and layered data encryption. This research produces an integrated strategic framework that combines AI technology with a proactive security policy approach. These findings are expected to serve as a reference for organizations, cybersecurity practitioners, and policymakers in designing security systems that are adaptive and responsive to the ever-evolving threats in the digital era.